(untitled) (Revista Apotheke, 2024)
The investigative process aimed to penetrate the before, during and after the teaching actions aimed at studying Visual Arts teaching methodologies, in the Degree in a public Higher education institution, within the Brazilian federal education network. The research took place in the first half of 2023. Used the cartographic method of investigation and documents such as lesson plans, on-site observations, records of artistic practices, student narratives, photographs of experiences troughout the period. The body, senses, emotions, affections, self-narratives, experience, inclusion and bullying were themes studied alongside experiences materialized in artistic productions. Reflecting on teaching strategies, developing dialogue and listening, extratcting the most from experiences without losing authenticity and creativity were some of the elements highlighted by students in the processes.